FAKTOR YANG MEMPENGARUHI PENYEBARAN BERITA PALSU: STUDI KASUS KOTA BATAM - Agus Yanto; Eric Eric; Jerry Khu; Daniel Prisman; Dimas Firmansyah Nasution (Universitas Teuku Umar, 2022)
With the development of today's technology, information will quickly spread. Because of this, false information easily reaches the public. People who get false information often share it again without knowing that the information is fake. Therefore, this study aims to determine the level of trust of WhatsApp users in false information among the people of Batam. This quantitative research was conducted by distributing online questionnaires and as many as 326 respondents were involved in this study. The method used in this research is the regression method with the help of SPSS software. This study concludes that most people do not seem to care about the truth of the information being spread and will immediately share the information because they think the information is important for others.